KAJI EKSPERIMENTAL ALAT PENGERING TENAGA SURYA DENGAN VARIASI SUDUT KONSENTRATOR CERMIN DATAR DAN SUDUT RIBLETS UNTUK PELAT ABSORBER - Daryanto, Eka; ., Suprapto (JURNAL PENELITIAN SAINTIKA, 2014)
This research aims to design and test equipment Solar Dryer and Bio Gas (APTMBG) based; 1) the influence of the angle and the angle concentrator peprindahan ribelts on the rate of heat that occurs in the solar thermal energy absorber channels and fish drying chamber, 2). surface roughness on absorbernya plate with the drying process using solar energy and drying with solar-biomass energyThe results showed that the drying of fish products using heat sources of biomass and gas have had advantages and disadvantages. The test results showed it by using solar thermal drying diruang temperatures average only reached 40-500C. The condition of maximum solar heat can not be achieved because at the time of data collection in August and September in the field occurred rainy season. While testing the use of heat from biomass (charcoal) and drying gas temperature in the drying chamber reaches an average of 50-700C. To dry salted fish which has a water content of 100% up to 10% takes 3-4 hours with mass consumption of biomass (charcoal) 2 kg.